TEACHER’S ROLE TRANSFORMATION IN THE BLENDED LEARNING ENVIRONMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the transformation of teachers’ roles in blended learning environments, where traditional face-to-face instruction is integrated with digital and online learning components. The study explores how teachers shift from being primary knowledge providers to facilitators, mentors, and designers of learning experiences. It highlights the skills required for effective classroom management, technological integration, and personalized instruction. The article also discusses challenges and opportunities related to professional development, digital literacy, and pedagogical innovation in blended learning contexts.